THE LOSS OF KINETOPLASTIC DNA IN TWO SPECIES OF TRYPANOSOMATIDAE TREATED WITH ACRIFLAVINE - Steinert, M. (The Rockefeller University Press, 1967)
The effects of acriflavine on two species of Trypanosomatidae, Crithidia luciliae and Trypanosoma mega, have been investigated. It has been observed that kinetoplastic (i.e. mitochondrial) DNA is lost in a high percentage of acriflavine-treated cells. Resting flagellates, from stationary-phase or hemin-deficient cultures, are considerably more resistant to the acridine than are flagellates from a log-phase culture. When the kinetoplast has retained some DNA and still remains visible in stained smears, it appears reduced in size, and its ultrastructure is extremely abnormal: the DNA fibrils, clearly visible in normal kinetoplasts, are condensed; they appear as an electron-opaque, apparently homogeneous mass, separated from the membranes by a space of low electron-opacity. Analyses of DNA extracts, with high speed centrifugation in CsCl density gradients, revealed that the satellite band, presumably kinetoplastic DNA, is lost by trypanosomes grown for 5 days in the presence of acriflavine. Radioautography was used to study the effects of acriflavine on thymidine-(3)H incorporation in C. luciliae. At the concentration which affects the kinetoplast specifically, the dye produces an 87% inhibition of thymidine incorporation in this organelle. The kinetics of this inhibition suggest a direct effect on replication. No decrease in incorporation occurs in the nucleus. These results lead to the conclusion that loss of kinetoplastic DNA is due to continued growth and cell division in the absence of kinetoplastic DNA replication. Several hypotheses are discussed concerning the specificity of the dye's action upon the replication of extrachromosomal DNA.